Some New Species of the Subfamily Trachyleberidinae (Ostracoda) from the Maastrichtian – late Eocene of the Middle East - Al-Sheikhly, Sa’ad S. (Iraqi Journal of Science, 2022)
Five new ostracod species belonging to the subfamily Trachyleberidinae have been described. They are Paragrenocythere monilis and Peloriops levisulcata from the Maastrichtian of Iraq; Oertliella petraensis from the early Palaeocene (middle – late Danian) of Jordan; Reticulina syriaensis from the Palaeocene of Syria and Reticulina ninurta from the middle – late Eocene of Iraq.